Analysis on Behavior Grounding Electrode Resistance base on Profiling Method. Issue 1 (May 2020) - Hashim, N. H.; Arshad, S. N. M.; Halim, N. H.; Wooi, C. L.; Ariffen, AM; Anuar, Aminudin; Aqilah Sofiyah Hasni, Nur; Abu Bakar, Osman
Abstract: An earthing system or known as grounding system in an electrical installation where by the grounding system connects specific parts of that installation with the Earth's conductive surface for safety and functional purposes. It is the process of transferring the immediate discharge with the aid of the low resistance wire of the electrical energy directly to the earth. It is really an important role playing in electrical system part as grounding system give protection during fault or lightning occur. In addition, grounding system also give protection for human electrical appliance and building from electrical shocks due to electrical fault or lighting occur. In this research will shows that to identify the best location to install the grounding electrode. This method is used on 10 x 10 meters which is 121 point will be investigated. The result of 0.3m, 0.6m, and 0.9m were analyzed using MATLAB software to produce profiling and shows the perfect location to install the Grounding system electrode.